A NEW ROUTE FOR THE SYNTHESIS OF FUNCTIONALIZED β-LACTAM ANTIBIOTIC - IPSITA MOHANRAM; JYOTSNA S. MESHRAM (International Journal of Pharma and Bio Sciences, 2015)
We report an efficient and novel synthesis of functionalized β-lactam in three steps through Ugi-4CR in the presence of fluorite as catalyst followed by [2+2] cyclocondensation reaction. The reaction has been performed in one-pot under benign conditions. A microwave-mediated synthesis followed by conventional stirring at room temperature achieved the desired compounds 9(a-f) in good yields of about 82-89%. All the compounds 9(a-f) were screened in vivo anti-inflammatory and in vitro antibacterial activities for their potential biological efficacy. The screening data reveals that Ugi derived lactam derivatives 9a, 9c and 9e are potent anti-inflammatory agents while 9a, 9c, 9d, 9e and 9f are potential antibacterial agents. All synthesized compounds 9(a-f) were proved to be extremely active biological agent with respect to reference drugs used.